A brief review of hole transporting materials commonly used in perovskite solar cells - Li, Song; Cao, Yong-Li; Li, Wen-Hua; Bo, Zhi-Shan (Rare metals, 2021)
Perovskite solar cells (PSCs) have been brought into sharp focus in the photovoltaic field due to their excellent performance in recent years. The power conversion efficiency (PCE) has reached to be 25.2% in state-of-the-art PSCs due to the outstanding intrinsic properties of perovskite materials as well as progressive optimization of each functional layer, especially the active layer and hole transporting layer (HTL). In this review, we mainly discuss various hole transporting materials (HTMs) consisting of HTL in PSCs. The progress in PSCs is firstly introduced, then the roles of HTL playing in photovoltaic performance improvement of PSCs are emphasized. Finally, we generally categorize HTMs into organic and inorganic groups and demonstrate both their advantages and disadvantages. Specially, we introduce several typical organic HTMs such as P3HT, PTTA, PEDOT:PSS, spiro-OMeTAD, and inorganic HTMs such as copper-based materials (CuO x , CuSCN, CuI, etc.), nickel-based materials (NiO x ), and two-dimensional layered materials (MoS 2 , WS 2 , etc.). On basis of reviewing the reported HTMs in recent years, we expect to provide some enlightenment for design and application of novel HTMs that can be used to further promote PSCs performance.